Host‐Guest Complexes of Dodeka(ethylene)octamine: Prediction of Ion Selectivity by Quantum Chemical Calculations IX1. Issue 10 (24th January 2019) - Puchta, Ralph; Walther, Daniel; März, Matthias; Begel, Svetlana; van Eldik, Rudi
Abstract : In this contribution we investigated the ion complexation of Bühl's cryptand, dodeka(ethylene)octamine by quantum chemical methods (B3LYP/LANL2DZp). This cryptand is an isomer of a well‐known Lehn‐type cryptand [TriPip222]. The ion selectivity was determined based on the energetic criteria derived by model reactions starting from solvated metal ions and empty dodeka(ethylene)octamine, and by comparing the M –N bond length in [ M ⊂ dodeka(ethylene)octamine] m + and [ M (NH3 )6 ] m + . We calculated that Bühl's cryptand will complex best Na + followed by Li + as alkaline cations and Ca 2+ followed by Mg 2+ as alkaline earth metal ions. Based on this data we conclude that Bühl's cryptand offers a smaller cavity to nest ions than the Lehn‐type [TriPip222]. Abstract :